2008
DOI: 10.1016/j.yhbeh.2007.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Use of cognitive strategies in rats: The role of estradiol and its interaction with dopamine

Abstract: Accumulating evidence suggests a role for estrogen in the use of a particular cognitive strategy when solving a maze task. In order to confirm the role of estrogen in this phenomenon, ovariectomized (OVX) female rats receiving either high ( approximately 90 pg/ml) or low ( approximately 32 pg/ml) circulating levels of 17beta-estradiol benzoate (E2) performed a plus maze task for a reward. Consistent with previous research, OVX rats receiving low levels of E2 utilized a striatum-mediated response strategy while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 45 publications
5
50
0
5
Order By: Relevance
“…Estrogen has been reported to have dif-ferent effects on striatal-and hippocampal-mediated learning [10], such that estrogen facilitates hippocampal-mediated learning while it interferes with striatally-mediated learning. It has been further suggested that the interaction between estrogen and dopamine influences the use of striatally-or hippocampally-mediated strategies in the performance of a cognitive task [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen has been reported to have dif-ferent effects on striatal-and hippocampal-mediated learning [10], such that estrogen facilitates hippocampal-mediated learning while it interferes with striatally-mediated learning. It has been further suggested that the interaction between estrogen and dopamine influences the use of striatally-or hippocampally-mediated strategies in the performance of a cognitive task [13].…”
Section: Discussionmentioning
confidence: 99%
“…While it is likely that the crew will consist of both male and female astronauts, there has been little research on the effects of exposure to HZE particles on central nervous system function and cognitive performance in female subjects. Both exposure to HZE particles [4][5][6][7][8][9] and the gonadal hormone environment [10][11][12][13][14][15] can affect neuronal function and cognitive performance. As such, it is possible that males and females may respond to HZE particle irradiation differently.…”
Section: Introductionmentioning
confidence: 99%
“…An infusion of amphetamine, an indirect-dopamine agonist, into the hippocampus biases rats toward using place memory, but an amphetamine infusion into the STR biases rats toward using response memory (Packard and White 1991). Interestingly, when estrogen levels are high, either during the proestrus phase of the estrous cycle or following E2 replacement in ovariectomized females, rats are biased toward using place memory (Korol and Kolo 2002, Quinlan et al 2008). More recently we showed that an infusion of E2 directly into the PFC biases female rats towards use of place memory, indicating that E2 acts rapidly (<15 minutes) to affect memory system bias, possibly via reciprocal projections with the STR and hippocampus (Almey et al 2014).…”
Section: Estrogens Affect Dopamine-dependent Diseases and Cognitivmentioning
confidence: 99%
“…The No E2 and Low E2 groups also received an injection of sesame oil vehicle every second day as an injection control. These doses were chosen to mimic the levels of estrogen in estrous and proestrous young cycling rats; blood levels of the hormones at these doses are similar to endogenous levels in rats (Almey et al, 2013;Madularu et al, 2014;Overpeck et al, 1978;Quinlan et al, 2008). The high dose of E2 was administered in a phasic manner to also mimic the phasic nature of high estrogen naturally; estrogen fluctuation (and not continuous administration) has been shown to affect hippocampal-mediated processes (Lipatova et al, 2014).…”
Section: Drugsmentioning
confidence: 99%